The Influence Of Da’wah Messages And Mass Media Dissemination On Environmental Consciousness Among Populations Adjacent To Batang Gadis National Park - Muhammad Isa; Susi Evanita (Jurnal Info Sains : Informatika dan Sains, 2024)
This study is predicated upon the persistent environmental degradation perpetrated by communities inhabiting the periphery of Batang Gadis National Park (Indonesian: Taman Nasional Batang Gadis [TNBG]). The investigation was undertaken in five villages within the West Panyabungan District, which share a direct boundary with TNBG. The primary objective of this research is to elucidate the impact of da’wah messages and mass media dissemination on the environmental consciousness of the local populace residing near TNBG. Employing a quantitative methodology, the study utilized a structured questionnaire as its principal instrument. The research encompassed a population of 183 individuals, from which a sample of 65 respondents was drawn. Data analysis was conducted using multiple regression techniques and processed through SPSS software. The findings reveal a significant simultaneous influence of da’wah messages and mass media dissemination on the environmental consciousness of the communities neighboring TNBG. However, when assessed individually, it was determined that da’wah messages have a discernible impact on environmental awareness, whereas mass media dissemination does not exhibit a statistically significant effect. To foster heightened environmental consciousness among the local populace, intensifying environmental preservation campaigns through da’wah activities in collaboration with religious leaders is recommended.